Assisting peer on distance learning as intervention to improve students’ performance in mathematics: a cross-over study - Janinne D. Villa Del Rey-Coderias; Polemer M. Cuarto (Journal of Education and Learning (EduLearn), 2026)
The global health pandemic necessitated a rapid shift to distance learning, prompting a need to explore effective instructional strategies. This study aimed to investigate the comparative effectiveness of assisting peer on distance learning (APDL) and conventional modular distance learning (CMDL) on grade 10 students’ performance in solving problems on circles and coordinate geometry. A quasi-experiment using cross-over design was employed, involving a control group (n=20) using CMDL and an experimental group (n=20) using APDL. Data were collected through pre-tests and post-tests and were treated statistically using paired and unpaired t-tests and cross-over t-test. Results revealed a significant difference in post-test scores, with the APDL group outperforming the CMDL group, without carry-over effects. Both methods contributed to knowledge acquisition, but peer collaboration significantly enhanced problem-solving abilities. The study concludes that APDL is an effective strategy for enhancing mathematical performance in distance learning. Therefore, it is recommended that APDL be integrated into distance learning programs, teacher training should be provided, and further research should be conducted to optimize its implementation and explore its long-term effects.